ANALISIS BELANJA PEMERINTAH DAERAH BERBASIS VALUE FOR MONEY TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN KERINCI - Ramah Ramah; Iskandar Sam; Misni Erwati (Jurnal Daya Saing, 2026)
This study aims to analyze the local government expenditure performance ofKerinci Regency based on the value for money concept, encompassing economy andefficienci, as well as its impact on the Human Development Index (HDI). This researchis motivated by the importance of managing local government budgets with focus notonly on budget absorption but also on developmental impacts felt by the community.Regional autonomy under Law Number 1 of 2022 grants local governments broadauthority in managing finances while demanding accountability and efficiency. Theindependent variables are local government expenditure and value for money (economyand efficiency), while the dependent variable is the HDI. The results show that: (1)expenditure management during 2014–2024 falls into the economical category; (2)efficiency fluctuated throughout the period — 6 years were categorized as efficient(2014, 2015, 2017, 2018, 2021, 2022) and 5 years as inefficient (2016, 2019, 2020,2023, 2024), though overall efficiency performance can be considered fairly good.